2016
DOI: 10.2147/opth.s90449
|View full text |Cite
|
Sign up to set email alerts
|

Value of optical coherence tomography in the detection of macular pathology before the removal of silicone oil

Abstract: PurposeTo assess the pathological macular changes with optical coherence tomography (OCT) before the removal of silicone oil (SiO) in eyes that had undergone pars plana vitrectomy for complicated forms of retinal detachment (RD).Patients and methodsSubjects included 48 patients (51 eyes) with complicated RD including proliferative vitreoretinopathy, proliferative diabetic retinopathy, recurrent RD, penetrating trauma, uveitis, giant retinal tears, and macular holes. All the eyes had undergone SiO injection. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
0
8
1
Order By: Relevance
“…In the present study, the incidence of CME after vitrectomy with SO tamponade was found to be 36.2%, which is higher than that reported by previous studies (13.6% to 27.5%) [ 11 12 13 14 ]. Upon comparative evaluation of preoperative and postoperative SD-OCT images of 46 eyes that received vitrectomy with SO tamponade, Bae et al [ 12 ] reported CME in 9 (19.6%) eyes before SO removal.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In the present study, the incidence of CME after vitrectomy with SO tamponade was found to be 36.2%, which is higher than that reported by previous studies (13.6% to 27.5%) [ 11 12 13 14 ]. Upon comparative evaluation of preoperative and postoperative SD-OCT images of 46 eyes that received vitrectomy with SO tamponade, Bae et al [ 12 ] reported CME in 9 (19.6%) eyes before SO removal.…”
Section: Discussioncontrasting
confidence: 79%
“…Kiss et al [ 13 ] reported the development of CME after SO tamponade only in eyes with RD caused by PVR (7 / 39 eyes, 17.1%). Rashad et al [ 11 ] reported a 27.5% incidence of CME (14 of 51 eyes) using SD-OCT–based diagnosis. Karahan et al [ 14 ] reported a 13.6% incidence of CME (3 of 22 eyes) among patients with rhegmatogenous RD who received SO tamponade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Optical coherence tomography (OCT) is a non-invasive technology that provides in vivo high-resolution measurements of the macular thickness that enables clinicians to detect and monitor subtle changes in macular thickness. 2 - 7 Normative macular thickness was obtained by several studies using OCT. 8 , 9 Spectral domain OCT (SD-OCT) systems are faster and more sensitive than time-domain OCT (TD-OCT) systems that provide an improved resolution, more accurate segmentation, and data points. 10 - 12 One important feature of SD-OCT raster scans is its ability to reconstruct a fundus-like image as soon as the scan is acquired.…”
mentioning
confidence: 99%
“…We read with great interest the article titled “Value of optical coherence tomography in the detection of macular pathology before the removal of silicone oil” by Rashad et al 1 The authors have evaluated the optical coherence tomography (OCT) findings before the removal of silicone oil (SiO). We congratulate the authors for this well-organized study and would like to contribute to their findings.…”
mentioning
confidence: 99%